Analysis of body type, dietary intake, and cardiorespiratory function in college soccer players - Desty Ervira Puspaningtyas; Yuni Afriani; Silvi Lailatul Mahfida; Arta Farmawati; Wara Kushartanti (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study aims to analyze body type, dietary intake, and cardiorespiratory function of college soccer players. A total of 32 players (20 players from Yogyakarta State University and 12 players from Gadjah Mada University) were involved in this study. The study was carried out in April - June 2014. Body type, or somatotype, was calculated based on anthropometric measurements (weight, height, epicondylar humerus and epicondylar femur width, arm and calf circumference, and subcutaneous fat thickness). 24-hour food recall was used to measure the athlete's dietary intake. VO2max was used to describe the athlete's cardiorespiratory function, and it was measured by yo-yo intermittent recovery test level 2. The data were analyzed descriptively using statistical software. More than three-quarter of the players had normal nutritional status with body mass index=21.54±1.84. The majority player's body type was balanced mesomorph (2.6-4.4-2.7). Balanced mesomorph players and ectomorphic mesomorph players had adequate energy and protein intake (2,623.83 kcal energy and 75.82 g protein for balanced mesomorph players; 2.724.68 kcal energy and 84.83 g protein for ectomorphic mesomorph players). Ectomorphic mesomorph players had the highest VO2max level (52.37±2.61 ml/kg/min). Soccer players with a mesomorph component supported by good energy and protein intake have the most optimal VO2max level.